Human resource strategies for the high growth entrepreneurial firm - Tansky, Judith W.; Heneman, Robert L. (Research in human resource management., 2006)
This volume not only illustrates the research that is being done in the area of human resources in entrepreneurial firms but it raises many issues that exemplify the complexity of the topic. It is not a case of small versus large firms. There are small established firms, small start-up firms and small high growth firms. As pointed out by Alvarez and Molloy these firms differ with established firms dealing with risk while high growth firms deal with uncertainty. These firms vary in ownership based on family ownership, ownership by founder, or some type of privately held stock ownership. These firms also vary based on how they handle people issues: structure versus lack of structure; the traditional HR functional approach versus the use of people management practices; person-job fit versus person- organization fit; ability and work experience versus integrity and conscientiousness; work processes and bureaucracy versus agility and adaptability; tasks versus roles; in-house professionals versus reliance on third-party vendors; traditional pay versus variable pay; short-term orientation of incentives versus long-term orientation of incentives; and many more.